2020
DOI: 10.1002/mbo3.1052
|View full text |Cite
|
Sign up to set email alerts
|

Individual Nudix hydrolases affect diverse features of Pseudomonas aeruginosa

Abstract: Nudix proteins catalyze the hydrolysis of pyrophosphate bonds in a variety of substrates and are ubiquitous in all domains of life. The genome of an important opportunistic human pathogen, Pseudomonas aeruginosa , encodes multiple Nudix proteins. To determine the role of nine Nudix hydrolases of the P. aeruginosa PAO1161 strain in its fitness, virulence or antibiotic resistance mutants devoid of individual enzymes were constructed and analyzed for growth rate, moti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…Furthermore, nudix proteins catalyze the hydrolysis of pyrophosphate bonds and have a demonstrated role in bacterial fitness and virulence. Mutants of Pseudomonas aeruginosa devoid of individual nudix hydrolases were more sensitive to killing by oxidative stress/H 2 O 2 and showed less virulence [ 52 ]. Moreover, Rhs proteins play a crucial role in the interaction between bacteria and host cell.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, nudix proteins catalyze the hydrolysis of pyrophosphate bonds and have a demonstrated role in bacterial fitness and virulence. Mutants of Pseudomonas aeruginosa devoid of individual nudix hydrolases were more sensitive to killing by oxidative stress/H 2 O 2 and showed less virulence [ 52 ]. Moreover, Rhs proteins play a crucial role in the interaction between bacteria and host cell.…”
Section: Resultsmentioning
confidence: 99%
“…There was significant downregulation of stringent starvation protein A (SspA) in the PAO1 Δfap SIP group; this protein provides adaptation to stringent stress responses in a new environment ( 39 ). A nudix pyrophosphatase (PA5176) relieved ROS generation and also contributed toward motility and pathogenicity ( 40 ). PA5176 was found to be upregulated ~8-fold in PAO1 pFap attached cells.…”
Section: Resultsmentioning
confidence: 99%
“…Using HMMER-based approach, 146 candidate OGs were identified, whilst the HHsearch-based approach picked up 564 candidates, including 136 being identified by both approaches (Table 2, full details in Supplemental Table S2). Among the 136 candidates are known housekeeping nucleosidases, such as the NUDIX enzyme NudC (OG1452), the Sirtuin CobB3 (OG752), the purine nucleosidase RihA (OG2649), and cyclic-AMP phosphodiesterase CpdA (OG3903) (Drabinska et al, 2020; Fuchs et al, 2010; Gallego-Jara et al, 2021; Petersen and Moller, 2001). In addition, both searches identified the TIR T3E HopAM1 (OG6638) (Eastman et al, 2022) and the ART T3E HopU1 (OG9885) (Fu et al, 2007).…”
Section: Resultsmentioning
confidence: 99%
“…Although we focused on identifying T3Es in this study, it would be interesting to determine if any of these non-T3E NADases are hrp -regulated and thus may also contribute to pathogenesis. For example, Drabinska et al (2020) identified multiple NUDIX enzymes in the animal opportunistic pathogen P. aeruginosa that are involved in virulence, production of the toxin pyocyanin, and resistance to oxidative stress.…”
Section: Discussionmentioning
confidence: 99%